Building Information Modelling (BIM): design process and interoperability in projects / Aimi Ashikin Hanib - Hanib, Aimi Ashikin (2015)
Building Information Modelling (BIM) is the computer based to stimulate construction project management from design process until maintenance. BIM tools are to create 3D model with rich of information. The work flow of design process using BIM as a tools are administer of collaborative among designer/consultant. Therefore, implementing BIM in projects involved full commitment from all the stakeholders, consultant and contractor include supplier integration during development and design stage. This research to achieve the aim of ‘to explore the appropriate design process and the concept of interoperability at design process stage in Malaysian construction industry either for government or private sector in implementing projects using BIM’. Reassuring the aims are achieve, three (3) objectives had establish that: 1) to identify process of BIM at project design stage; 2) to investigate the concept of interoperability in BIM; and 3) to identify challenges occurred in design process and interoperability of using BIM. Through literature review and engage in-depth interviews conducted, there is four (4) respondent from public and private sector. It was conclude that, all organisation are looking forward to improve the design stage in future by using BIM as a tools with enhancing the procurement system, produce more expertise and understand the BIM definition also to have BEP or Malaysia National Guideline. Interoperability is concept define as standardising the software conversion between two different software or more which related to integration of data exchange. The interoperability concept are related with human collaboration to improve the standardising of data sharing and transfer. Here, collaborative and interoperability are play as main role during design stage to produce 3D model with finalised clash analysis for construction stage. It has been notice that BIM in Malaysia AEC industry are still at early stage in implementation. There are several challenges were faced during design stage. Nevertheless, design process issue is progressively improving in BIM implementation in the nearest future by setting up the guidelines and change people mind set of BIM users in construction players widely.